A study on the translator‘s omissions and instances of adaptation in the Old English Orosius: The case of Alexander the Great - Omar Khalaf (Filologia Germanica)
This paper focuses on a hitherto neglected aspect of the Old English Orosius, namely the omissions of certain passages of the Latin source-text by the Anglo-Saxon translator. This essay proposes to chart such omissions systematically and to present a comprehensive interpretation of the modes of adaptation of the Latin source by the Old English translator, focusing in particular on a number of case-studies which are especially suggestive of the selection process.